News media and investor sentiment over the long run - Alan J. Hanna; John D. Turner; Clive B. Walker (Queen's University Centre for Economic History (QUCEH), 2017)
This paper studies the effect of investor sentiment on the London stock market on a daily basis over the period 1899 to 2010. We use a broad mix of reporting from the Financial Times as our proxy for investor sentiment. The main contribution of this paper is threefold. First, newspaper commentary, which was sentiment-laden, but information-light, in the Financial Times affects returns. Second, we find evidence that sentiment plays a role in propagating price movements, particularly during bull markets. Third, we find little evidence that the effect of sentiment on the market differs in bear versus bull markets.
Keywords: G12; N23; N24; 330; news media; investor sentiment; stock market; bull; bear